Access for peritoneal dialysis in neonates and infants. Issue 1 (January 1990) - Lewis, M A; Houston, I B; Postlethwaite, R J
Abstract : A new catheter for peritoneal dialysis in neonates and infants was used on 28 occasions in 17 patients. Advantages over other catheters included easy safe introduction over a guide wire, absence of early leakage of dialysate, and the ability to change the catheter without creating a second abdominal wound.